Translational GTPase BipA Is Involved in the Maturation of a Large Subunit of Bacterial Ribosome at Suboptimal Temperature - Goh, Kwok Jian; Ero, Rya; Yan, Xin-Fu; Park, Jung-Eun; Kundukad, Binu; Zheng, Jun; Sze, Siu Kwan; Gao, Yong-Gui (Frontiers in Microbiology, 2021)
BPI-inducible protein A (BipA), a highly conserved paralog of the well-known translational GTPases LepA and EF-G, has been implicated in bacterial motility, cold shock, stress response, biofilm formation, and virulence. BipA binds to the aminoacyl- (A) site of the bacterial ribosome and establishes contacts with functionally important regions of both subunits, implying a certain role relevant to ribosome, such as ribosome biogenesis and/or conditional protein translation. When cultured at suboptimal temperatures, the E. coli bipA genomic deletion strain (ΔbipA) exhibits defects in growth, swimming motility, and ribosome assembly, which can be complemented by a plasmid borne bipA supplementation or the genomic rluC deletion. Based on the growth curve, soft agar swimming assay, and ribosome profiles, mutation of the catalytic residue His78 rendered plasmid borne bipA unable to complement its deletion phenotypes. Interestingly, truncation of the C-terminal loop of BipA exacerbates the aforementioned phenotypes, demonstrating the involvement of BipA in ribosome assembly or its function. Furthermore, tandem mass tag-mass spectrometry analysis of ΔbipA strain proteome revealed upregulations of a number of proteins (e.g. DeaD, RNase R, CspA, RpoS, and ObgE) implicated in ribosome biogenesis and RNA metabolism, and these proteins were restored to wild-type levels by plasmid borne bipA supplementation or the genomic rluC deletion, implying BipA involvement in RNA metabolism and ribosome biogenesis. We have also determined that BipA interacts with ribosome 50S precursor (pre-50S), suggesting its role in 50S maturation and ribosome biogenesis. Taken together, BipA demonstrates the characteristics of a bona fide 50S assembly factor in ribosome biogenesis.